INITIAL DEVELOPMENT OF EUCALYPTUS CLONE I144 (Eucalyptus grandis x Eucalyptus urophylla) IN RESPONSE TO FOLIAR AND SOIL FERTILIZATION - Firmano, Ruan Francisco; Barzan, Renan Ribeiro; Fregonezi, Gustavo Adolfo de Freitas; Antonangelo, João Arthur; Melo, Thadeu Rodrigues de; Delalibera, Gabriel de Carvalho (Scientia Agraria, 2017)
The nutritional management of eucalyptus (Eucalyptus spp.) is one of the main factors responsible for the success of its cultivation. We aimed to evaluate the initial growth and nutritional status of eucalyptus clone I144 (Eucalyptus grandis x Eucalyptus urophylla) submitted to foliar fertilizers application containing boron-B, iron-Fe and bio-stimulant and via soil application of nitrogen-N and phosphorus-P doses. The experiment has been conducted in a rural private property of Tamarana, Parana (PR) in a subdivided plots experiment design with four replications (n=4). The plots treatments were boron, boron+iron, boron+iron+bio-stimulant applications under algae (Ecklonia maxima) presence and a control (water). The subplots treatments were composed by the application of 100, 150 and 250 g plant-1 rates of 10-20-00 (N-P2O5-K2O) and a control (0 g plant-1 of 10-20-00). It was evaluated the height and diameters of plants at 45, 78, 117, 150 and 235 days after planting (DAP) and the leaves nutrient content (N, potassium-K, calcium-Ca, magnesium-Mg, sulfur-S, copper-Cu, zinc-Zn, manganese-Mn and Fe) at the end of the cultivation. The fertilization via soil did not interfere on either growth or macronutrients contents. On the other hand, the combined application of foliar fertilizers has increased the macronutrients contents without interfering on growth parameters.